Determination and optimization of the machining parameters of the welded areas in moulds - (:unkn) unknown (ACADEMIC JOURNALS, 2011)
In this study, the parameters of surface roughness, cutting temperature and cutting forces in the milling of the repaired welding regions of DIN 1.2344 hot work tool steel, which was used in mould manufacturing, with end mills coated multilayer TiAIN were examined experimentally. The effects of the feed rate, cutting speed and depth of cut on surface roughness, cutting temperature and cutting force were searched. In order to optimize the cutting conditions, Taguchi optimization method was applied. The effect of each parameter on the obtained results was determined by the use of analysis of variance (ANOVA). The relationship of the dependent parameters and independent parameters was modelled with regression analysis. It was seen that this experiment study made many a contribution to the machinability of DIN 1.2344 hot work tool steel, which was repaired by welding, with carbide end mills coated with multilayer TiAIN and accelerated the improvement in the performance of the cutting tool.
Keywords: The welded areas; machining parameters; Taguchi optimization method; anova; regression analysis; COATED CARBIDE TOOLS; STEEL; D2; SPEED; HRC; PERFORMANCE